Highly active and selective hydrodeoxygenation of oleic acid to second generation bio-diesel over SiO2-supported CoxNi1−xP catalysts. (1st July 2019) - Zhang, Zhige; Bi, Guican; Zhang, Hongdan; Zhang, Aiping; Li, Xin; Xie, Jun
Highlights: CoNiP/SiO2 was a high efficiency hydrodeoxidation catalyst. CoNiP/SiO2 was highly selective to the target product C17 . The synergistic effect of Co and Ni greatly improved the catalytic activity. CoNiP/SiO2 provides theoretical basis for bio-diesel field. Abstract: Bio-fuels have been proposed as an ideal alternative fuel to conventional fossil fuel due to the advantages of renewability and low pollution. Herein, to greatly enhance the catalytic activity and selectivity of for the production of second generation biodiesel, designed and developed five kinds of catalysts with different ratios (3/1, 5/3, 1/1, 3/5, 1/3) of Co to Ni. The composite catalyst was characterized by XRD, XPS and HRTEM techniques. The activity and selectivity of the catalyst were evaluated by the hydrodeoxidization of oleic acid. It was found that the hydrodeoxygenation activity and selectivity of Cox Ni1−x P/SiO2 catalyst was closely related to the proportion of Co/Ni. The selectivity of C17 followed the decreasing order: 3/5 > 1/3 ≈ 1/1 > 5/3 > 3/1 (Co/Ni ratios). Clearly, among all the samples, the catalyst with 3/5 Co/Ni ratio exhibits the best conversion rate and selectivity of 97% and 86% for the production of C17, respectively. The high activity and selectivity of Cox Ni1−x P/SiO2 were dominantly attributed to the synergistic effects and the uniform dispersion of Co and Ni species on the SiO2 supports. In particular, the Cox Ni1−x P/SiO2 shows the more advantages than the high activity for Ni-based catalysts and high selectivity for Co-based catalysts. It is expected that the catalyst has the great potential to be used in the practical industrial production.